Compounds specific to Aspalathus linearis protects the diabetic heart against oxidative stress: a mechanistic study - Dludla, Phiwayinkosi Vusi (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhD)--Stellenbosch University, 2016